(untitled) (Texas Journal of Philology, Culture and History, 2025)
Eastern miniature art is not just a form of visual art but also a means of reflecting aesthetic taste, cultural values, and historical events. In miniature paintings, color and composition play a crucial role in revealing the semantic meaning of the artwork. This article discusses the analysis of colors and the principles of composition in miniature art.